EFFECT OF NSAIDS IN COMBINATION WITH SERRATIOPEPTIDASE VS. DIODE LASER ON POST ENDODONTIC PAIN IN PATIENTS WITH VITAL AND NON-VITAL TEETH: A RANDOMISED CLINICAL TRIAL. - Dr. Pradnya Nagmode; Dr. Sayali Gosavi; Dr. Sathish Abraham; Dr. Nitin Lokhande; Dr. Gayatri Gundap (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Aim: Endodontic treatment encompasses the holistic approach to pre-, intra, and post-operative care, including addressing the risk of chronic post-operative endodontic pain. This pain is prevalent, multifactorial, and potentially linked to acute periapical inflammation resulting from various factors during treatment. Serratiopeptidase affiliated with the class of drugs identified as non-steroidal anti-inflammatory drugs (NSAID) is employed to alleviate pain, especially post-traumatic inflammation, in a variety of illnesses. Therefore, the present study is formulated to assess the influence of NSAIDs in combination with serratiopeptidase compared with diode laser on post-endodontic pain in patients with vital and non-vital teeth.Methods: A randomized clinical trial was carried out in the department of conservative dentistry and endodontics. After fulfilling the eligibility criteria, 40 patients were involved in this study. Patients who met the requirements for inclusion were then randomly split into two distinct categories, in which 20 patients were in Group A (NSAIDs with serratiopeptidase) and 20 patients were in Group B – diode laser).Results: In total, 40 patients were involved in this study. The postoperative pain score after both treatment groups A and B showed a difference in pain scores that was statistically significant at all-time points (p < 0.0001). In group A, the proportion of patients experiencing no pain significantly increased over time. In group B, there was a remarkable trend in pain severity among patients over various time intervals.Conclusion: The study findings indicated that the effectiveness of diode laser therapy was less effective than NSAIDS used in conjunction with Serratiopeptidase.